Data Slavery or Business as usual? : Analysis of data rights by balancing fundamental rights and freedoms within the realms of surveillance capitalism and decision-making theories - Paukamainen, Paavo (My University, 2022)
As the world heads towards the fourth industrial revolution with increasingly complex technological data-based solutions, fundamental rights require an assessment. This research contributes to this need by conducting empirical research with an international scope. The primary legal sources include conventions on human rights. Private and public parties use data for multiple purposes, including commercial and political aspirations. The use of data – if continued in a current manner – threatens individual freedom and, consecutively foundations of a democratic society. To assess where the borders lie – when business as usual turns into data slavery – the definitions of slave and slavery with the existing international legal instruments prohibiting slavery call for scrutiny. The outcome of this research is that data slavery already exists but in most parts of the world, data slavery is not the right word to describe the situation. Data exploitation is a better word to describe situations where people are being utilised using their data but where the utilisation – control over the data source – does not exceed the threshold of data slavery. Everyone should be more aware of how their data is used to improve the situation. Also, international harmonisation concerning conventions and their interpretations should be improved. Furthermore, the legal status of personal data as an asset comparable to the property should be developed further to provide clear rights for the original data sources, who should primarily be called data owners.
Keywords: data, data slavery, data exploitation, democracy, freedom, slave, slavery, technology